An assessment of the relationship between sweetener prices and high fructose corn syrup deliveries in the United States - Philip Lynn Kennedy; Pablo A. Garcia-Fuentes; Gustavo F. C. Ferreira (Journal of Applied Economics, 2021)
This paper uses an application of the Bertrand model to explain the relationship between HFCS deliveries and the prices of HFCS-42 and sugar. It finds that the HFCS deliveries and the prices of HFCS-42 and refined sugar are cointegrated over the period 1994:q1-2020:q1. The main results, based on the estimated long-run elasticities, show that a one percent increase in the price of HFCS-42 decreases HFCS deliveries by 0.153 percent. One implication of this result is that it would be helpful for the HFCS industry to prevent large increases in the HFCS price, which would prevent large decreases in HFCS deliveries and its share in the U.S. sweetener market. In addition, the price of sugar does not have a significant effect on HFCS deliveries.
Keywords: 330; Deliveries; high fructose corn syrup; prices; sugar; United States